Relationship between Interest Rate Movements and Common Stock Returns - Chen, Jun (2006)
The volatility of interest rate and the risks from exposure to such volatility has made it a quite important subject of study in this area. Most existing studies examining the phenomenon of interest rate sensitivity have focused on its influence on the stock returns of banks and financial institutions. In general, it is certainly true that due to the nature of their activities. Nevertheless, such interest rate volatility also affects firms which are non-financial in nature. One of the main contributions of this dissertation is that we have attempted to analyze the interest rate exposure of both financial as well as non-financial firms. Moreover, it will use a three factor regression model, whereby we regress the returns on any chosen S&P500 index on returns of the S&P 500 composite index, changes in the domestic and global interest rates.